To the inhabitants of New-York, and all the British colonies. New-York, 20th April 1775 : the following very interesting accounts were yesterday received by the snow Gen. Johnson, Capt. Dean, in 31 days from England . (LLMC-digital (Series), 1775)
Containing extracts from three letters from London, dated February-March 1775, informing the colonists of events and persons inimical to their interests both in England and America.